Pengaruh Pola Asuh Permisif terhadap Kemandirian Anak Usia Dini - Salsa Havida Nurli; Pupu Chotimah; Desvi Wahyuni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to conduct a study regarding Permissive Parenting Patterns on the independence of early childhood. Permissive parenting is a parenting pattern that involves parents in children's lives with little control or limits. This parenting pattern is a parenting pattern with minimal control, resulting in a lack of children's ability to control themselves. The method used in this research is a qualitative method with the approach used is a case approach with descriptive analysis. Permissive parenting is a parenting style in which the role of parents is directly involved with the child, but this involvement only ends in giving them an understanding of something or controlling them. Parents will give freedom to children according to each child's wishes, with the result of parenting that children do not have the opportunity to learn to control themselves, they will always expect and even enforce their wishes. It can be concluded that permissive parenting does not always produce children with poor independence, but this occurs because there are more obstacles than democratic and positive parenting.